2022
DOI: 10.1186/s12879-022-07890-6
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin compared with placebo in the clinical course in Mexican patients with asymptomatic and mild COVID-19: a randomized clinical trial

Abstract: Background Despite the development and application of vaccines against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) around the world, the scientific community is still trying to find some therapies to avoid or ameliorate the fatal evolution of the Coronavirus disease 2019 (COVID-19). Since the publication of the potential use of ivermectin as a treatment against the disease, a pleiad of information about it has been published. However, the evidence is not strong or weak enough t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Regarding the effect of the drug in reducing viral load, our clinical study on the effect of three days of ivermectin in reducing the viral load in mild cases of ambulatory patients showed its advantage over placebo in a double-blind randomized control study 50 . Similar results were obtained in a study in Mexico demonstrating a significant decline on day 5 51 , while other studies did not find any advantage of the drug 52 "The main argument against using ivermectin is that the level of existing evidence for its positive effect is based mainly on studies lacking a high standard of rigorous methodology 53,54 .…”
Section: Discussionsupporting
confidence: 58%
“…Regarding the effect of the drug in reducing viral load, our clinical study on the effect of three days of ivermectin in reducing the viral load in mild cases of ambulatory patients showed its advantage over placebo in a double-blind randomized control study 50 . Similar results were obtained in a study in Mexico demonstrating a significant decline on day 5 51 , while other studies did not find any advantage of the drug 52 "The main argument against using ivermectin is that the level of existing evidence for its positive effect is based mainly on studies lacking a high standard of rigorous methodology 53,54 .…”
Section: Discussionsupporting
confidence: 58%
“…Seventeen of the thirty-three studies reported on MV requirement (n = 6049 participants) [ 10 , [24] , [25] , [26] , 59 , 60 , 64 , 65 , [68] , [69] , [70] , [71] , [72] , 75 , 76 , 81 , 82 ], and significant difference was observed between the two groups (RR 0.67, 95% CI 0.47–0.96, I 2 = 0%; Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 disease severity was asymptomatic/mild in 12 randomized controlled trials, moderate in 1, mild and moderate in 17, severe in 2, and moderate and severe in 1. Studies were done in 19 countries: Argentina (n = 3 studies) [ [58] , [59] , [60] ], Bangladesh (n = 2) [ 61 , 62 ], Brazil (n = 1) [ 10 ], China (n = 1) [ 63 ], Colombia (n = 1) [ 64 ], Egypt (n = 3) [ 23 , 65 , 66 ], India (n = 3) [ [67] , [68] , [69] ], Iran (n = 3) [ 26 , 70 , 71 ], Israel (n = 1) [ 72 ], Italy (n = 1) [ 22 ], Japan, (n = 1) [ 73 ], Malaysia (n = 1) [ 24 ], Mexico (n = 2) [ 74 , 75 ], Nigeria (n = 1) [ 76 ], Pakistan (n = 2) [ 77 , 78 ], Spain (n = 1) [ 79 ], Thailand (n = 2) [ 25 , 80 ], Turkey (n = 1) [ 81 ], and USA (n = 3) [ 21 , 82 , 83 ]. Of all 33 studies, 7 had an overall high risk of bias, 13 had some concerns of bias, and 13 had a low risk ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations